The Development Of Accounting Information System Based On Excel In Helping CV. Ladi Collection Preparing Their Financial Statement - Putri Wulanditya; Riski Aprillianita (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2018)
Microenterprises in Indonesia is showing increasing progress, especially the printing industry. This study wanted to know what is the description of printing business cycle, accounting records on financial transactions, calculation of production costs and operating income. Research method used is study case at CV. Ladi Collection through field observation, interview, and documentation. Data analysis technique used is qualitative descriptive. From study result in CV. Ladi Collection, there are 2 types of business namely screen printing and school badge production. Accounting recording has been done but only limited to Accounts Receivable Bookkeeping. Many of cash receipts transactions from cash sales are derived from screen printing orders and expenditures were not stored and recorded. Solution on production costs calculation for CV. Ladi Collection is using job order costing for screen printing service and job product costing for badge production. This research also produces Excel design For Accounting (EFA), which consists of 7 sheets of the navigation sheet, beginning balance, journal, ledger, income statement, financial position statement, and depreciation.